Mediating the intersections of organizational routines during the introduction of a health IT system - Novak, Laurie; Brooks, JoAnn; Gadd, Cynthia; Anders, Shilo; Lorenzi, Nancy (European journal of information systems, 2012)
Public interest in the quality and safety of health care has spurred examination of specific organizational routines believed to yield risk in health care work. Medication administration routines, in particular, have been the subject of numerous improvement projects involving information technology development, and other forms of research and regulation. This study draws from ethnographic observation to examine how the common routine of medication administration intersects with other organizational routines, and why understanding such intersections is important. We present three cases describing intersections between medication administration and other routines, including a pharmacy routine, medication administration on the next shift and management reporting. We found that each intersection had ostensive and performative dimensions; and furthermore, that IT-enabled changes to one routine led to unintended consequences in its intersection with others, resulting in misalignment of ostensive and performative aspects of the intersection. Our analysis focused on the activities of a group of nurses who provide technology use mediation (TUM) before and after the rollout of a new health IT system. This research offers new insights on the intersection of organizational routines, demonstrates the value of analyzing TUM activities to better understand the relationship between IT introduction and changes in routines, and has practical implications for the implementation of technology in complex practice settings.